Guinea : Request for Disbursement Under the Rapid Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for Guinea. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2020)
Guinea is being severely affected by the COVID-19 pandemic. A local outbreak is spreading rapidly, adding pressure to the fragile social context and putting a strain on the health system. Containment measures have started to negatively impact domestic economic activity. Furthermore, the sharp slowdown in China (Guinea's main export market) has hindered mining exports and tax revenues, putting pressure on Guinea's external and fiscal position. Since the completion of the fourth ECF review, worsening global conditions and the local outbreak have deteriorated Guinea's short-term outlook. Real growth is expected to sharply decelerate to 1.4 percent in 2020.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet